Sistem Manajemen Ticketing pada Penyelenggara Pertandingan Liga Sepak Bola Berbasis Near Field Communication (NFC) yang Terintegrasi Web - Atok Hardiyanto (Politeknik Negeri Malang, 2017)
There is a lot of ticket brokering. The ticket leakage rate can be minimized to a minimum with the help of an automatic gate that will open when the audience balance is sufficient, this is shown on the website. QoS measurement using Wireshark software from the process of sending data from raspberry pi to the web server. The results showed that the maximum reading distance of the NFC reader was 2.5 cm in the position of the test tag above the reader. Based on the QoS test results, the average data packet sending with very good speed in the ITU-T category is <150 ms. In testing the distance of 26 meters, 5 meters and 3 meters between the stadium internet (wifi) source to the node at the gate because from the 3rd measurement the distance gets <150 ms according to the ITU-T standard. The results obtained are 130,588 ms, 123,493 ms and 116,818 ms. For device performance from the results of NFC testing, motor, LCD and web server can run continuously. The web server can only accommodate users of approximately 100 users at the same time with 3 clicks